2016
DOI: 10.1097/spv.0000000000000308
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Urinary Tract Infection After Midurethral Sling: A Retrospective Study

Abstract: In this population, preoperative recurrent UTI was the only modifiable risk factor associated with an increased risk of postoperative recurrent UTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
1
3
3
2
Order By: Relevance
“…We found an average 30-day postoperative UTI rate of 3.3%, which was lower than that documented by most other studies in the range of 10-20%. [2][3][4][5] In contrast to our data demonstrating no clinically significant differences in 30-day complications and reoperations, there were notable differences in the rate of postoperative UTIs based on race and ethnicity. Compared with American Indian or Alaska Native patients and both Hispanic and non-Hispanic White patients, Black or African American patients had fewer UTI diagnoses despite having a higher proportion with comorbidities that could increase their risk of developing a UTI (ie, diabetes).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found an average 30-day postoperative UTI rate of 3.3%, which was lower than that documented by most other studies in the range of 10-20%. [2][3][4][5] In contrast to our data demonstrating no clinically significant differences in 30-day complications and reoperations, there were notable differences in the rate of postoperative UTIs based on race and ethnicity. Compared with American Indian or Alaska Native patients and both Hispanic and non-Hispanic White patients, Black or African American patients had fewer UTI diagnoses despite having a higher proportion with comorbidities that could increase their risk of developing a UTI (ie, diabetes).…”
Section: Discussioncontrasting
confidence: 99%
“…With 13.6% of women affected by stress urinary incontinence (SUI), midurethral sling operations are among of the most common urogynecologic procedures with 260,000 performed annually in the United States 1 . Despite generally being a well-tolerated outpatient procedure associated with a low risk of morbidity, reported rates of urinary tract infection (UTI) are high, in the range of (10–20%) 2–5 . Urinary tract infections account for more than 8 million office visits per year, longer hospital stays for inpatients, and increased antibiotic use 6,7 .…”
mentioning
confidence: 99%
“…Prior studies have reported a wide range of PO-UTI rates following POP/SUI surgery, with variation in surgical events, UTI definition, and period of interest. One large retrospective study of 7,461 midurethral sling procedures looked at RUTI within 1 year after surgery and found a 3.5% PO-RUTI rate based on positive urine culture of >10 5 CFU/mL, 21 which was lower than our 4.8% rate after SUI surgery. Their 1.2% preoperative RUTI rate was also lower than our 3.7% rate.…”
Section: Discussioncontrasting
confidence: 74%
“…El objetivo principal de este estudio fue determinar la frecuencia de infección de vías urinarias posterior a la colocación de cinta medio uretral durante su primer año, infección de vías urinarias recurrente y los factores de riesgo, presentándose un 12.7% de IVU en el primer año postoperatorio, 3.4% de IVU recurrente, estos valores son similares a los reportados por Jessica Hammett, 12% y 3.5% respectivamente, (12) de igual manera en el meta-análisis de Schimpf et al, donde reportan incidencia de IVU 11%, (5) evaluaron 6286 pacientes, Nygaard et al, evaluaron 1252 paciente, reportan una incidencia del 7%-12% para IVU posterior a CMU y 2.4% de IVU recurrente, (6) frecuencias similares a las encontradas en este estudio, aumentando de esta manera la validez externa del mismo.…”
Section: Discussionunclassified
“…(11) A pesar de la frecuencia con la que se producen las IVU, hay relativamente pocos datos que evalúan los factores de riesgo de la IVU o la IVU recurrente en las poblaciones con CMU. (12) Los factores de riesgo asociados a la IVU posterior a CMU descritos son: la edad mayor de 65 años, uso de estrógeno vaginal, uso de sonda urinaria más de 6 semanas, obesidad mórbida, diabetes mellitus, incontinencia urinaria, obstrucción urinaria y cirugía urogenital previa. (13) Sin embargo a la fecha los resultados son controvertidos y no se han detectado parámetros urodinámicos asociados a la IVU postcolocación de CMU.…”
Section: Antecedentesunclassified